Analysis of the Effect of Credit Risk and Market Risk on Banking Capital Satisfaction during the Covid-19 Pandemic (Case Study on Commercial Banks In Indonesia) - Saezar Alamaint; Wisnu Mawardi (Journal of Business, Social and Technology, 2023)
The COVID-19 pandemic has posed significant challenges to the financial stability of banking institutions around the world. This research seeks to conduct an empirical study to determine the effect of credit risk and market risk on capital security. This study aims to examine (1) the effect of Credit Restructuring,Non-Performing Loans (NPL), Net Interest (NIM) on Capital Adequacy Ratio (CAR) (2) the effect of NPL, NIM on Return On Assets (ROA) (3) the effect of ROA on CAR and (4) the effect of NIM, NPL to CAR with ROA as the intervening variable. The sample for this research is commercial banks registered with OJK in 2020 that meet the research criteria. The method of analysis in this study is path analysis which is the development of multiple and bivariate regression analysis. The research results show thatCredit restructuring has a negative and insignificant effect, NPL has a negative and insignificant effect on CAR, NIM has a positive and not significant effect on CAR, NPL has a negative and significant effect on ROA, NIM has a positive and significant effect on ROA, ROA has a negative and significant effect on CAR, NPL has a direct influence on CAR through ROA, NIM has no effect on CAR through ROA.